RECONSTRUCTION OF THE FINANCIAL REPORT OF THE NURUL IMAN TEGALBARU PALERAN MOSQUE BASED ON PSAK NO. 109 - Septianingrum, Leny; Aspirandi, Rendy Mirwan; Nuha, Gardina Aulin (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study aims to reconstruct the financial statements of Masjid Nurul Iman, located in Paleran Village, Umbulsari District, Jember Regency, using the Statement of Financial Accounting Standards (PSAK) No. 109 on Zakat, Infaq, and Alms Accounting. As a non-profit religious institution, mosques have a moral and administrative obligation to present accountable, transparent, and standardized financial reports to enhance public trust. This research adopts a descriptive qualitative approach using documentation and interviews with mosque administrators. The results show that prior to the reconstruction, financial reporting was conducted manually and simply, without account classification or the preparation of comprehensive financial statements. After being reconstructed according to PSAK No. 109, the financial reports were systematically prepared, including the statement of financial position, activity report, fund changes report, and notes to the financial statements. This reconstruction positively influenced the administrators' awareness of the importance of professional and accountable financial management of religious funds. This study recommends that other mosques begin to implement applicable accounting standards to improve the effectiveness of mosque financial management.